The Effect of Land-Use Intensity on Surface Temperature in the Dongting Lake Area, China - Wenmin Hu; Weijun Zhou; Hongshi He (Advances in Meteorology)
Land use and its environmental effects can be quantitatively expressed with land-use intensity. In this study, a land-use intensity metric was improved using a geographic mapping method. The relationships between observed rapid changes in land use and temperature in the Dongting Lake area from 2001 to 2010 were examined. The results revealed the following features: (1) The temperature increased when the land-use intensity increased via a hierarchical transition owing to grass and forest land reductions of 26.25% and 11.74%, respectively; built-up land increased by 48.45%. (2) The temperature increase was driven more by the external environment than by land-use intensity changes. Human activities produced larger effects in the western region than in the eastern or central region of the study area, according to the observed variations in the centres of gravity for temperature and land-use intensity. (3) The temperature response to land-use intensity changes was more sensitive in low-altitude areas than in high-altitude areas; the response presented a north-south gradient, possibly due to socioeconomic and urbanisation differences.